1984
DOI: 10.1016/0167-4781(84)90128-3
|View full text |Cite
|
Sign up to set email alerts
|

DNA circles with cruciforms from Isospora (Toxoplasma) gondii

Abstract: We have isolated a closed circular duplex DNA fraction from theunicellular parasite Isospora (Toxoplasma) gondii and examined the purified DNA by electron microscopy. A major part of this circular DNA consists of 12-pm circles containing a cruciform with 0.5-pm tails. We also found 23-pm circles with the properties expected of head-to-tail dimers of the 12-/tm circles. Some of these dimers have two cruciforms with 0.4-ttm tails, some have one cruciform with 0.8-pm tails. When ethidium bromide was diffused into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
2

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 35 publications
1
16
0
2
Order By: Relevance
“…61,1997 EXTRACHROMOSOMAL DNA IN THE APICOMPLEXAConservation Snap-back and cross-hybridization experiments with fragments from the IR of the malarial circle provided evidence for conservation of the rDNA palindrome in two other genera of apicomplexans, namely, T. gondii and Eimeria tenella (122). These observations confirmed the suggestion of Borst et al (10) that the cruciform structure they observed in T. gondii circular DNA by electron microscopy was derived from palindromic rRNA genes. Hybridization and PCR experiments have also detected sequences corresponding to rpoB/C, tufA, ORF470, and trn in T. gondii and E. tenella, organized in the same way as in P. falciparum (19a).…”
Section: Codon Usagesupporting
confidence: 79%
“…61,1997 EXTRACHROMOSOMAL DNA IN THE APICOMPLEXAConservation Snap-back and cross-hybridization experiments with fragments from the IR of the malarial circle provided evidence for conservation of the rDNA palindrome in two other genera of apicomplexans, namely, T. gondii and Eimeria tenella (122). These observations confirmed the suggestion of Borst et al (10) that the cruciform structure they observed in T. gondii circular DNA by electron microscopy was derived from palindromic rRNA genes. Hybridization and PCR experiments have also detected sequences corresponding to rpoB/C, tufA, ORF470, and trn in T. gondii and E. tenella, organized in the same way as in P. falciparum (19a).…”
Section: Codon Usagesupporting
confidence: 79%
“…1, both spiramycin and azithromycin showed no effect after 1 day of treatment and only slight inhibition after 2 days. However, parasite growth was profoundly inhibited after 4 days with 50% inhibitory concentrations (IC50s) of 40 ng/ml for spiramycin and 12 ng/ml for azithromycin. Additional experiments ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Some of these are likely to be synthesized on noncytoplasmic ribosomes, but none is sensitive to macrolide antibiotics. In addition to the cytoplasmic ribosomal RNA genes encoded within the nuclear genome, T. gondii, like other coccidian parasites (35), appears to contain at least two additional classes of ribosomal RNA genes, encoded by the mitochondrial genome (present as a tandemly repeated 6-kb linear sequence in Plasmodium species [26]), and a plastid-like genome (a 35-kb circular molecule; [9,29,36,37]). At this stage it is not possible to directly link the cycloheximide-resistant spots with either the mitochondrion or the plastid-like genomes, but the observation that the Plasmodium mitchondrial DNA is much more heavily transcribed than the 35-kb plastid-like circle (Vaidya, A., personal communication) argues in favor of a mitochondrial origin (38).…”
Section: Discussionmentioning
confidence: 99%